A STUDY ON QUALITY OF WORK LIFE AT BIG BAZAAR, HYDERBAD (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In current scenario the importance of QUALITY OF WORK LIFE has beenincreasing. It describes about professional environment and humanistic values that are degradedto some extent. As professionals are unable to balance both their professional and personal life.This variation has made organization to make new policies; it leads to enhance job satisfactionand performance of employee. The level of performance has been referred to QUALITY OFWORK LIFE. It is a method in an organization that helps its members at all level to participateactively and efficiently. This study focuses on performance of employee. The parameters whichhave been selected to observe the QWL in this study are social factors, economic factors trainingand development, of the employees. The main objective of this study is to examine the variousfactors influencing QUALITY OF WORK LIFE at Big Bazaar. The sample size taken for thisstudy is 100 samples the methodology followed for taking sample is questionnaire method in BigBazaar at Hyderabad. The technique used for this sample is correlation. The variables used inthis test are quality of work life is an independent variable and performance of the employee isdependent variable.